Rat gastrointestinal tissues metabolize quercetin - Graf, Brigitte A; Ameho, Clement; Dolnikowski, Gregory G; Milbury, Paul E; Chen, Chung-Yen; Blumberg, Jeffrey B (The Journal of nutrition, 2006)
Quercetin and quercetin glycosides from food or dietary supplements appear in body tissues almost exclusively as glucuronated, sulfated, and methylated quercetin conjugates, suggesting that the in vivo bioactivity of quercetin may be due to its metabolites. In this study, pre- and postabsorptive metabolism of orally ingested quercetin was examined by comparing the metabolite pattern in gastrointestinal (GI) tissues, contents, and internal tissues. F344 rats (n = 6) were fed for 6 wk a diet containing 0.45% quercetin and the metabolite patterns were determined in the tissues and contents of stomach, small intestine, cecum, and colon and in liver, kidney, and plasma using LC-MS/MS. GI contents contained predominantly unmetabolized quercetin at 94-100%, whereas quercetin in GI tissues was present as 11 different sulfated, glucuronated, and methylated metabolites at 32% in stomach, 88% in small intestine, 27% in cecum, and 46% in colon. Quercetin was further metabolized postabsorption and found in liver, kidney, and plasma almost exclusively as sulfated methyl-quercetin glucuronide. The unique pattern of quercetin metabolites in each GI tissue indicates extensive biotransformation before absorption and distribution in rats.